Tellurium in Late Permian‐Early Triassic Sediments as a Proxy for Siberian Flood Basalt Volcanism. (16th November 2020) - Regelous, Marcel; Regelous, Anette; Grasby, Stephen E.; Bond, David P. G.; Haase, Karsten M.; Gleißner, Stefan; Wignall, Paul B.
Abstract: We measured the concentrations of trace elements in Late Permian to Early Triassic sediments from Spitsbergen. High mercury concentrations in sediments from the level of the Permo‐Triassic Mass Extinction (PTME) at this location were previously attributed to the emplacement of the Siberian Traps Large Igneous Province and used to link the timing of volcanism with the record of environmental change and extinction in these sediments. We investigated the use of the moderately to highly volatile, siderophile elements Ni, Zn, Cd, Sb, Te, Re, and Tl as proxies for the intensity of Siberian volcanism. These trace elements, like Hg, have high concentrations in volcanic gas compared to crustal rocks. Tellurium is highly enriched at the PTME, and Te/Th ratios increase by a factor of ∼20 across the PTME, similar to the variation in Hg/total organic carbon (TOC) in the same samples. Te/Th and Hg/TOC values imply that Siberian volcanism initiated at the onset of the PTME, coincident with the start of the δ 13 Corganic excursion and abrupt warming. Based on Te and Hg, most Siberian volcanism occurred between the two phases of the PTME boundary (a period of less than 100 ky), but also continued into the Early Triassic. The duration of Siberian volcanism inferred from Te/Th and Hg/TOC is shorter than that indicated by recent high‐precision U‐Pb ages of Siberian intrusive and extrusive rocks. Te concentrations and Te/Th ratios in sediments represent a useful new proxy for volcanism, which can be used to link the marine sedimentary record with large volcanic events on land. Key Points: Tellurium is enriched in sediments from the Late Permian Extinction (LPE) to Permian‐Triassic Boundary interval in Spitsbergen Tellurium and mercury are volcanogenic in origin, Te/Th ratios in sediments may represent a new proxy for volcanism Te and Hg imply short time interval for Siberian Traps volcanism, with most intense period initiating at the LPE